2009
DOI: 10.1002/jcp.21992
|View full text |Cite
|
Sign up to set email alerts
|

20,23‐dihydroxyvitamin D3, novel P450scc product, stimulates differentiation and inhibits proliferation and NF‐κB activity in human keratinocytes

Abstract: We have examined effects of the 20,23-dihydroxyvitamin D3 (20,23(OH)2D3), on differentiation and proliferation of human keratinocytes and the anti-inflammatory potential of 20,23(OH)2D3 from its action on nuclear factor-κB (NF-κB). 20,23(OH)2D3 inhibited growth of keratinocytes with a potency comparable to that for 1,25-dihydroxyvitamin D3 (1,25(OH)2D3). Cell cycle analysis showed that this inhibition was associated with G1/G0 and G2/M arrests. 20,23(OH)2D3 stimulated production of involucrin mRNA and inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
138
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 95 publications
(153 citation statements)
references
References 48 publications
15
138
0
Order By: Relevance
“…Along with the primary products of CYP11A1 action on vitamin D3, 17,20(OH) 2 D3, 20,22(OH) 2 D3, and 20,23(OH) 2 D3, we have a unique set of derivatives all containing a 20-hydroxyl group plus one additional hydroxyl group at every position on the side chain, except C21 (note that C26 and C27 are equivalent). All of these 20-hydroxy derivatives have been shown to be biologically active (Zbytek et al, 2008;Janjetovic et al, 2009Janjetovic et al, , 2010Janjetovic et al, , 2011Li et al, 2010;Slominski et al, 2010Slominski et al, , 2011Slominski et al, , 2012aTang et al, 2010a;Tuckey et al, 2011;Kim et al, 2012;Lu et al, 2012;Wang et al, 2012). The low catalytic efficiency of CYP27B1 toward 20(OH)D3 is greatly enhanced when the second hydroxyl group is added toward the end of the side chain, as seen for 24,20(OH) 2 D3, 20,25(OH) 2 D3, and 20,26(OH) 2 D3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the primary products of CYP11A1 action on vitamin D3, 17,20(OH) 2 D3, 20,22(OH) 2 D3, and 20,23(OH) 2 D3, we have a unique set of derivatives all containing a 20-hydroxyl group plus one additional hydroxyl group at every position on the side chain, except C21 (note that C26 and C27 are equivalent). All of these 20-hydroxy derivatives have been shown to be biologically active (Zbytek et al, 2008;Janjetovic et al, 2009Janjetovic et al, , 2010Janjetovic et al, , 2011Li et al, 2010;Slominski et al, 2010Slominski et al, , 2011Slominski et al, , 2012aTang et al, 2010a;Tuckey et al, 2011;Kim et al, 2012;Lu et al, 2012;Wang et al, 2012). The low catalytic efficiency of CYP27B1 toward 20(OH)D3 is greatly enhanced when the second hydroxyl group is added toward the end of the side chain, as seen for 24,20(OH) 2 D3, 20,25(OH) 2 D3, and 20,26(OH) 2 D3.…”
Section: Discussionmentioning
confidence: 99%
“…Via binding to the vitamin D receptor, these compounds can inhibit keratinocyte, melanoma, leukemia, breast, and liver cancer cell proliferation; promote differentiation; and display antiinflammatory activity by decreasing nuclear factor-ĸB activity (Zbytek et al, 2008;Janjetovic et al, 2009Janjetovic et al, , 2010Janjetovic et al, , 2011Li et al, 2010;Slominski et al, 2010Slominski et al, , 2011Slominski et al, , 2012aTang et al, 2010a;Tuckey et al, 2011;Kim et al, 2012;Lu et al, 2012;Wang et al, 2012). Importantly, all three of these derivatives lack calcemic activity in rodents, even at relatively high doses (Slominski et al, , 2013aWang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They also display strong antiproliferative and prodifferentiation effects on a range of cells, including keratinocytes and melanoma and leukemia cells, and an inhibitory action on nuclear factor-B activity (Zbytek et al, 2008;Janjetovic et al, 2009Janjetovic et al, , 2010Slominski et al, 2010Slominski et al, , 2011, identifying 20(OH)D as a potential therapeutic or adjuvant agent for a number of hyperproliferative and inflammatory diseases. In this study, we have found that 22(OH)D 3 acting through the VDR also shows antiproliferative and, to a limited degree, prodifferentiation ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The two major products of vitamin D 3 metabolism by P450scc, 20(OH)D 3 and 20,23(OH) 2 D 3 , have been tested on a range of skin and other cell types, and they have many but not all of the properties of the hormonally active form of vitamin D 3 , 1,25(OH) 2 D 3 , acting as partial receptor agonists (Zbytek et al, 2008;Janjetovic et al, 2009Janjetovic et al, , 2010Slominski et al, 2010;Tang et al, 2010a). Properties in common with 1,25(OH) 2 D 3 on skin cells include inhibition of proliferation and stimulation of differentiation of epidermal keratinocytes, and inhibition of nuclear factor-B activity via the stimulation of the expression of inhibitor of nuclear factor-B ␣.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently documented that the cytochrome P450scc-derived vitamin D analogs, 20(OH)D 3 and 20,23(OH) 2 D 3 , possess many of the properties of 1,25(OH) 2 D 3 such as the inhibition of proliferation, the promotion of differentiation, and suppression of inflammation, despite lacking the 1␣-hydroxyl group usually seen in vitamin D receptor agonists (Zbytek et al, 2008;Janjetovic et al, 2009Janjetovic et al, , 2010Slominski et al, 2010). Of particular note is our finding that 20(OH)D 3 lacks calcemic activity in rats but adding a 1␣-hydroxyl group to it partially returns the calcemic activity .…”
Section: Discussionmentioning
confidence: 99%